EP816 TRPV1 and PTEN expression is related to poor prognosis in epithelial ovarian cancer. (1st November 2019) - Chay, DB; Han, GH; Cho, H; Kim, J-H
Abstract : Introduction/Background: Transient receptor potential vanilloid type-1 (TRPV-1) was previously reported to be associated with cancer. This study explored the expression of TRPV-1 and PTEN in epithelial ovarian cancer and evaluated its clinical significance. Methodology: Immunohistochemical (IHC) staining analyses of TRPV-1 and PTEN were performed using tissue microarray (TMA) constructed from 198 ovarian cancer and 47 borderline ovarian tumor samples. The clinical significance was evaluated by comparing the data with various clinicopathologic characteristics, including survival of patients with epithelial ovarian cancer. Results: TRPV-1 and PTEN expression was significantly higher in ovarian cancer compared to borderline ovarian tumor and normal human ovarian surface epithelium (HOSE) (both p <0.001). Spearman's rank correlation analysis revealed that TRPV-1 expression shows significant correlation with PTEN expression in ovarian cancer (Spearman's rho=0.276, p <0.001). Multivariate analysis indicated that advanced FIGO stage (III–IV) (hazard ratio=2.66 [95% CI, 1.01–6.99], p =0.046), TRPV-1 expression (hazard ratio=3.23 [95% CI, 1.06–9.80], p =0.038), PTEN expression (hazard ratio=2.98 [95% CI, 1.61–5.40], p <0.001) and combined TRPV-1/PTEN (hazard ratio=3.37 [95% CI, 1.85–6.13], p <0.001) were independent prognostic factors for overall survival. Conclusion: This study reveals the association between TRPV-1 and PTEN expression with epithelial ovarian cancer and shows that these biomarkers predicts poor prognosis. The findings of this study warrants future research evaluating its clinical usefulness. Disclosure: Nothing to disclose.